SLOW DEEP PURSED-LIPS BREATHING EXERCISE ON VITAL LUNG CAPACITY IN POST-EXTUBATION PATIENTS IN THE INTENSIVE CARE UNIT - Heru Supriwandani; Mardiyono Mardiyono; Warijan Warijan (Belitung Nursing Journal, 2018)
Background: The incidence of respiratory failure reaches 20-75 cases per 100,000 population each year with mortality rate reaching 30-50%. Provision of respiratory assistance with mechanical ventilation is provided with an indication of the inability of the respiratory function for optimal alveolar ventilation. Efforts to restore lung oxygenation ventilation function can be done through breathing exercises and are expected to improve pulmonary ventilation function. Objective: This study was to examine the effectiveness of the modified Slow Deep Pursed-Lips Breathing Exercise (SDPLBE) on vital lung capacity in patients post-extubation of mechanical ventilators. Methods: This was a true experimental study with pretest posttest control group design. Thirty respondents were selected using stratified random sampling, with 15 samples assigned in the experiment and control group. Peak flow meter was used to measure vital lung capacity (FEV1 value). Repeated measures ANOVA was used for data analysis. Results: There was a significant difference on respondent's vital lung capacity after given slow deep pursed lips-breathing exercise at each session from session 1 to session 8 (p=0.000). However, both groups were not yet able to achieve ≥ 400 mL / min, but the experiment group was closer to the normal value (369) than the control group. Conclusion: Slow Deep Pursed-Lips Breathing Exercise may increase vital lung capacity in patients post-extubation of mechanical ventilator.